Mass islamization of peasants in Bosnia: Demystifications - Moačanin, Nenad (Array, 1999)
Bosnian peasants have adopted islam en masse mainly as a consequence of the poorly developed food production. That fact has not been perceived as yet but in random remarks. Narrative and archival sources supporting this idea are abundant.